Análisis del impacto de la política por pago de la calidad al litro de leche a las áreas económico-financiera y social a los centros de acopio del sector norte del cantón Cayambe periodo (2008-2013) - Sánchez Guerrero, Katherine Estefanía (2015)
The present work contains a financial-economic and social analysis of milk production area, in the northern part of Cayambe, taking as main variables the policy established by the government in the ministerial agreement 394 of payment for quality to a liter of milk and National plan of Good Living 2013-2017. The analysis is performed using the methodology of a case study, based on previous studies. The analysis was performed in the period of 2008-2013, in order to analyze the individual and associative impact of these mentioned variables. The information was obtained through surveys at the storage centers of the zone as well as producers. Further details could be obtained through socialization and observation. As a result it was found that production costs are high individually and due to the associativity it has reduced considerably. However in spite of the benefit of the associativity, they do not cover production costs at the current price, considering that costs of labor are high because it is a production that requires a lot of sacrifice. Moreover, it was observed a great development in the social field, in areas such as illiteracy, inclusion, environmental sustainability and also ratifying the democratic and popular power, improving the quality of life for people of these communities. The development of partnerships in the search for better profits is recommended for the same.